Characterizing the Access of Cholinergic Antagonists to Efferent Synapses in the Inner Ear - Lee, Choongheon; Sinha, Anjali K.; Henry, Kenneth; Walbaum, Anqi W.; Crooks, Peter A.; Holt, Joseph C. (Frontiers in Neuroscience, 2021)
Stimulation of cholinergic efferent neurons innervating the inner ear has profound, well-characterized effects on vestibular and auditory physiology, after activating distinct ACh receptors (AChRs) on afferents and hair cells in peripheral endorgans. Efferent-mediated fast and slow excitation of vestibular afferents are mediated by α4β2*-containing nicotinic AChRs (nAChRs) and muscarinic AChRs (mAChRs), respectively. On the auditory side, efferent-mediated suppression of distortion product otoacoustic emissions (DPOAEs) is mediated by α9α10nAChRs. Previous characterization of these synaptic mechanisms utilized cholinergic drugs, that when systemically administered, also reach the CNS, which may limit their utility in probing efferent function without also considering central effects. Use of peripherally-acting cholinergic drugs with local application strategies may be useful, but this approach has remained relatively unexplored. Using multiple administration routes, we performed a combination of vestibular afferent and DPOAE recordings during efferent stimulation in mouse and turtle to determine whether charged mAChR or α9α10nAChR antagonists, with little CNS entry, can still engage efferent synaptic targets in the inner ear. The charged mAChR antagonists glycopyrrolate and methscopolamine blocked efferent-mediated slow excitation of mouse vestibular afferents following intraperitoneal, middle ear, or direct perilymphatic administration. Both mAChR antagonists were effective when delivered to the middle ear, contralateral to the side of afferent recordings, suggesting they gain vascular access after first entering the perilymphatic compartment. In contrast, charged α9nAChR antagonists blocked efferent-mediated suppression of DPOAEs only upon direct perilymphatic application, but failed to reach efferent synapses when systemically administered. These data show that efferent mechanisms are viable targets for further characterizing drug access in the inner ear.